2021
DOI: 10.1136/jnnp-2020-325361
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory impairment as an early marker of Parkinson’s disease in REM sleep behaviour disorder: a systematic review and meta-analysis

Abstract: Olfactory impairment and rapid eye movement sleep behaviour disorder (RBD) are prodromal symptoms of Parkinson’s disease (PD) that may be associated with each other. This review aims to investigate the significance of olfaction in the diagnosis and prognosis of patients with RBD and to assess moderating factors affecting olfactory performance. We searched articles on olfaction in RBD and PD in five electronic databases. We identified 32 studies for the systematic review and used 28 of those, including 2858 par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 61 publications
0
14
0
Order By: Relevance
“…Olfactory dysfunction typically presents as one of the earliest events. It is the most specific predictor among nonmotor manifestations for recognising patients at short-term risk for PD and DLB 8. Additionally, the severity of autonomic symptoms was suggested to be associated with an accelerated rate of phenoconversion and putaminal DAT abnormalities in patients with iRBD 5.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Olfactory dysfunction typically presents as one of the earliest events. It is the most specific predictor among nonmotor manifestations for recognising patients at short-term risk for PD and DLB 8. Additionally, the severity of autonomic symptoms was suggested to be associated with an accelerated rate of phenoconversion and putaminal DAT abnormalities in patients with iRBD 5.…”
Section: Discussionmentioning
confidence: 99%
“…Supplementary neuroimaging, electrophysiological, biofluid and genetic biomarkers are also proposed as promising candidates 7. However, limited clinical trials have attested to the reliability of those markers with unsolved discrepancies, and only one meta-analysis identified the predictive value of hyposmia 8…”
Section: Introductionmentioning
confidence: 99%
“…Based on the evidence of injury-induced neurogenesis in the olfactory epithelium, it is logical to presume that accumulated physiological deterioration, as an outcome of lifestyle, could negatively influence neurogenesis in the olfactory epithelium causing olfactory decline through multiple cell types. Emerging experimental evidence even indicates the participation of non-neuronal cells in olfactory processing and odor perception that precede neurodegenerative pathology [ 44 , 115 ]. Therefore, the overall evaluation of olfactory dysfunction in combination with additional symptoms while considering multiple environmental and genetic factors for added risk could provide avenues for early therapeutic intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Rapid eye movement sleep behavior disorder (RBD) is an additional well-established clinical marker of PD. It is marked by an increment in odor threshold and significant impairment in odor identification and discrimination [ 115 ]. However, RBD is a recently identified marker where additional physiological and molecular information is still very limited.…”
Section: Neurodegenerative Diseasesmentioning
confidence: 99%
“…UPSIT performance was found to be a predictor of PD-MCI in this study, and this result is corroborated by several other studies (Hu et al, 2014 ; Fullard et al, 2016 ; Hogue et al, 2018 ; Roos et al, 2019 ; Pekel et al, 2020 ). Moreover, olfactory deficits were found to be a risk and predictor of dementia and PD in iRBD patients (Postuma et al, 2019 ; Lyu et al, 2021 ). It has been reported that PD-MCI is more likely to be associated with severe olfactory impairment than PD patients with normal cognition (Park et al, 2018 ), and an imaging study found entorhinal cortex atrophy in early, drug-naive PD patients with MCI (Jia et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%